Antibacterial Peptides from Plants: What They Are and How They Probably Work - Patrícia Barbosa Pelegrini; Rafael Perseghini del Sarto; Osmar Nascimento Silva; Octávio Luiz Franco; Maria Fátima Grossi-de-Sa (Biochemistry Research International)
Plant antibacterial peptides have been isolated from a wide variety of species. They consist of several protein groups with different features, such as the overall charge of the molecule, the content of disulphide bonds, and structural stability under environmental stress. Although the three-dimensional structures of several classes of plant peptides are well determined, the mechanism of action of some of these molecules is still not well defined. However, further studies may provide new evidences for their function on bacterial cell wall. Therefore, this paper focuses on plant peptides that show activity against plant-pathogenic and human-pathogenic bacteria. Furthermore, we describe the folding of several peptides and similarities among their three-dimensional structures. Some hypotheses for their mechanisms of action and attack on the bacterial membrane surface are also proposed.